Optimization model for Green Vendor Managed Inventory under disruptions - Baruah, Swapnali (2015)
Purpose: This dissertation reviews the literature in the field of Vehicle Routing Problem to analyze gaps in the literature of Green Vehicle Routing Problem and proposes a model in this field. This model bridges one such gap in literature to find optimal routes to a set of customers minimizing the total cost and taking carbon emission into consideration. There is no model in literature that caters to these objectives all at the same time. Methodology: Previous research has mostly focused on deterministic models and hardly considered carbon emission as part of the objective function, this study aims to bridge this gap and answers the research questions. To achieve this, a linear model was developed where the objective function was to minimize costs including transportation cost, penalty cost due to missed deliveries, inventory holding cost, ordering cost and cost due to carbon emission. The objective function was subjected to a number of constraints. This model was solved using a meta-heuristic method called Genetic Algorithm on a platform called MATLAB. Several simulations were run on a sample dataset from a case study. Findings: The findings from the research show that it is possible to find optimal routes while taking carbon emission into consideration. To confirm on the optimality of the solutions, simulations were run without taking carbon emission into consideration and it was observed that most of the times the transportation cost was lower when cost of carbon emission was taken into consideration compared to when carbon emission was not taken into consideration. This answers the research question that an ecological solution can be an economical solution as well. In the end theoretical contributions and managerial implications are discussed in detail. A brief on the future research opportunities are also discussed. Keywords: Vendor Managed Inventory, vehicle Routing Problem, Carbon emission, Green VMI